P58 Anonymous electronic IBD patient service feedback. (19th June 2022) - Downey, Louise; Rahmany, Sohail; Stammers, Matthew; Knibbs, Will; White, Laura; Felwick, Richard; Gwiggner, Markus
Abstract : Introduction: Collecting structured patient feedback is challenging, particularly during the pandemic with many virtual appointments. Our electronic IBD-patient feedback covers outpatient (OP), endoscopy and flare-line experiences. Methods: IBD patients provide anonymous feedback at the time-of-service contact. GATHER, a survey platform hosted by our institution, collects anonymous information via QR codes (scan QR codes for surveys), electronic links or handheld tablet. Demographics, disease characteristics and medication were noted in all 3 surveys. The OP survey collated clinic type/modality and feedback on individual health care professionals based on an adapted Royal College of Physicians questionnaire as well as preferences for future appointments. Endoscopy surveys gathered information on referral pathway, endoscopy type, treatment advice, length of wait and pre-test information. Flare line surveys allowed individual feedback on IBD nurses, assessed response time and outcomes. Patients' attitudes regarding use of our online portal My Medical Record (MyMR) were explored. All surveys allowed sign up for MyMR. Patients could leave individual comments. Results: Since September 2021, 425 patients responded. Figure 1 outlines the findings of the surveys. Conclusion: Electronic surveys are well accepted by our IBD patients and provides useful demographic data. It gives patients the option to inform the service of their preferences for future appointments and allows clinicians to get personal patient feedback for appraisals. Furthermore, it provides feedback on new services such as direct access endoscopy service and the acceptability of patient directed online healthcare (MyMR). Patient-centred feedback enables the user to help shape their future local IBD service.